Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1073/pnas.78.6.3688
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary membrane vesicles of paramecium contain the voltage-sensitive calcium channel.

Abstract: Calcium influx into ciliary membrane vesicles from paramecia was measured by using arsenazo MI as metallochromic indicator and as intravesicular calcium trap. Influx was rapid and reversible. In ciliary membrane vesicles from paramecium pawn mutants which lack the voltage-sensitive calcium channel, calcium influx was significantly less than in wild-type paramecia. These data demonstrate that the voltage-dependent calcium channel of paramecia is functional in a cell-free system and available for biochemical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Regarding that Magnesium is a natural calcium antagonist and a potent L-type calcium channel inhibitor [28] rationally the usage of MgSO 4 antagonized the Ca influx signal in the organisms. In addition, considering that the depolarizing Ca 2+ inward current is coupled to the generation of cGMP [24,25,26], the works agree with ours that blockade of Ca channels or cGMP pathway significantly reverse the L-arginine plus naloxone response. Although the role of cGMP has not been elucidated in most systems, it mediates many NO physiological effects as a signaling molecule in the nervous and cardiovascular systems [11,29].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Regarding that Magnesium is a natural calcium antagonist and a potent L-type calcium channel inhibitor [28] rationally the usage of MgSO 4 antagonized the Ca influx signal in the organisms. In addition, considering that the depolarizing Ca 2+ inward current is coupled to the generation of cGMP [24,25,26], the works agree with ours that blockade of Ca channels or cGMP pathway significantly reverse the L-arginine plus naloxone response. Although the role of cGMP has not been elucidated in most systems, it mediates many NO physiological effects as a signaling molecule in the nervous and cardiovascular systems [11,29].…”
Section: Discussionsupporting
confidence: 79%
“…Our previous results have also implicated NO in the morphine effect by NADPHdiaphorase cytochemistry [1]. It has been postulated that several NO-sensitive targets, including guanylyl cyclase, potassium channels and voltage gated calcium channels [21,22,23,24,25] are stimulated in invertebrates. Other studies using the ciliate protozoan Stentor have demonstrated that these types of microorganisms express a G protein-mediated response to morphine when stimulated mechanically [26].…”
Section: Discussionmentioning
confidence: 99%
“…All evidences favour Ca 2+ as the relevant signal, whereas formation of cGMP during ciliary reversal in Paramecium [50,54,55] may exert a modulatory effect only [45,[56][57][58][59][60]. In Paramecium, guanylate cyclase is distributed over the ciliary membrane [61], but cGMP rises during ciliary reversal induction only with considerable delay [56,62], at least ∼10 times slower than [Ca 2+ ] [55].…”
Section: [Ca 2+ ] Increase Originating From Depolarisation-dependent mentioning
confidence: 99%
“…Data obtained thus far indicate a possible role of phosphorylation/dephosphorylation cycles (Schultz et al, 1990). Ciliary reversal is triggered by increased free Ca2+ concentrations via activation of voltage-dependent Ca2+ channels localized in ciliary membranes (Cohen et al, 1990;Schultz et al, 1990;Thiele and Schultz, 1981;Eckert and Brehm, 1979).…”
Section: Introductionmentioning
confidence: 99%